2021
DOI: 10.3389/fneur.2021.682615
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hippocampal Subfield Asymmetry at 7T With Automated Segmentation in Epilepsy Patients With Normal Clinical Strength MRIs

Abstract: While the etiology of hippocampal sclerosis (HS) in epilepsy patients remains unknown, distinct phenotypes of hippocampal subfield atrophy have been associated with different clinical presentations and surgical outcomes. The advent of novel techniques including ultra-high field 7T magnetic resonance imaging (MRI) and automated subfield volumetry have further enabled detection of hippocampal pathology in patients with epilepsy, however, studies combining both 7T MRI and automated segmentation in epilepsy patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Of these, the DG and CA1 are the structures with the greatest reduction with respect to their counterparts in the contralesional hippocampus. Other structural MRI studies have also identified these two substructures as the most affected in this disease ( 53 , 54 ), also when compared with patients with non-epileptic controls and non-HS MTLE ( 53 , 55 , 56 ). This is also consistent with data from the ILAE histopathological classification study of MTLE-HS.…”
Section: Discussionmentioning
confidence: 67%
“…Of these, the DG and CA1 are the structures with the greatest reduction with respect to their counterparts in the contralesional hippocampus. Other structural MRI studies have also identified these two substructures as the most affected in this disease ( 53 , 54 ), also when compared with patients with non-epileptic controls and non-HS MTLE ( 53 , 55 , 56 ). This is also consistent with data from the ILAE histopathological classification study of MTLE-HS.…”
Section: Discussionmentioning
confidence: 67%
“…Prior work at 3 T has demonstrated structural alterations in the hippocampus and thalamus of patients with epilepsy. 18,[36][37][38][39] Independently, hippocampal [10][11][12][13] and thalamic 20 alterations have also been reported at 7 T. We expand on this literature by leveraging 7-T structural neuroimaging of both the hippocampus and the thalamus. We found that all ipsilateral hippocampal subfields (CA1, CA2, CA3, DG) as well as some ipsilateral (CM, MD) and contralateral (AV, Pul, MD) thalamic nuclei were significantly atrophied in our epilepsy cohort relative to controls.…”
Section: Epilepsy Patients Have Significant Bilateral Alterations In ...mentioning
confidence: 91%
“…[5][6][7] Volumetric changes, quantified through 3-T structural neuroimaging, have been demonstrated between controls and patients with epilepsy across these subfields. 8,9 More recently, ultra-high-field 7-T scanners with hippocampus-specific imaging protocols have been used to provide greater contrast in these subfields, allowing for the interrogation of more subtle volumetric, [10][11][12][13] functional, 14 and even neurotransmitter expression 15 changes.…”
Section: Introductionmentioning
confidence: 99%
“…Use of ultra-high field MRI scanners, such as those operating at 7-Tesla (7T), can allow for increased visualization of boundaries and delineation of subfields than conventional clinical strength scanners due to superior contrast and resolution at 7T ( 31 ). These high-field advantages can reveal structural subtleties which are below the threshold of detectability at clinical field strengths ( 32 ). There is a limited number of 7T studies examining hippocampal subfields in MDD and their segmentation methods include either manual tracings ( 33 ) or automated segmentation with FreeSurfer version 6.0 ( 29 , 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%